2021
DOI: 10.1021/acs.jpcb.1c01621
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of Diabetic and Non-Diabetic Peripheral Nerve Myelin Lipid Bilayers

Abstract: The multilayered myelin sheath is a critical component of both central and peripheral nervous systems, forming a protective barrier against axonal damage and facilitating the movement of nervous impulses. It is primarily composed of cholesterol (CHL1), phosphatidylcholine (PC), phosphatidylethanolamine (PE), phosphatidylserine (PS), phosphatidylinositol (PI), sphingomyelin (SM), and galactosylceramide (GalCer) lipids. For rat sciatic nerve myelin (part of the peripheral nervous system, PNS), it has been found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…It is known that patients with diabetes suffer from peripheral neuropathic pain, which is caused by peripheral neuropathy caused by increased blood glucose [ 41 ]. Studies have shown that diabetes leads to peripheral neuropathy by reducing phospholipid synthesis to induce myelin abnormalities in nerves [ 42 , 43 ]. In this study, serum glucose and other carbohydrates of serum in the CCI group showed significant increases in the CCI group, suggesting that NP may lead to abnormal energy metabolism and elevated blood glucose in the serum; elevated blood glucose may further inhibit phospholipid synthesis and finally exacerbate the pain response.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that patients with diabetes suffer from peripheral neuropathic pain, which is caused by peripheral neuropathy caused by increased blood glucose [ 41 ]. Studies have shown that diabetes leads to peripheral neuropathy by reducing phospholipid synthesis to induce myelin abnormalities in nerves [ 42 , 43 ]. In this study, serum glucose and other carbohydrates of serum in the CCI group showed significant increases in the CCI group, suggesting that NP may lead to abnormal energy metabolism and elevated blood glucose in the serum; elevated blood glucose may further inhibit phospholipid synthesis and finally exacerbate the pain response.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from plants, mammalian membrane models have been studied using the C36 lipid FF in our laboratory. Unlike plants whose major sphingolipids are glycosphingolipids, mammalian membranes contain more sphingomyelins (SMs) and ceramides (CERs). , The lipid composition can vary wildly depending on the species and organelles, which is evident from our models for ocular lens, stratum corneum (SC), , and peripheral nerve myelin . The modeling of the ocular lens focused on the influence of CHOL fraction and SM species where CHOL% ranged from 0 to 73 in the context of equal GPL/SM concentration.…”
Section: Mammalian Membrane Modelsmentioning
confidence: 99%
“…142,143 The lipid composition can vary wildly depending on the species and organelles, which is evident from our models for ocular lens, 144 stratum corneum (SC), 145,146 and peripheral nerve myelin. 147 The modeling of the ocular lens focused on the influence of CHOL fraction and SM species where CHOL% ranged from 0 to 73 in the context of equal GPL/SM concentration. Two sets of models were developed for the SC, corresponding to the short periodicity phase (SPP) and the long periodicity phase (LPP).…”
Section: ■ Mammalian Membrane Modelsmentioning
confidence: 99%
See 1 more Smart Citation